Institutional Capacities and Social Policy Implementation: Maternal Child Health and Nutrition Programmes in Argentina and Chile (1930-2000) (2013)
This article compares maternal child health and nutrition programmes in Argentina and Chile, focusing on long-term institutional features and the central neo-liberal trends organizing social reforms during the 1980s and the 1990s. Objective: To carry out a comparative study of the ransformations of Maternal Child Health and Nutrition Programmes, taking into account three intertwined issues: social policies, institutional capacity, and policy implementation. Methodology: The documentary analysis done in this article is framed in the structural force model of Carmelo Mesa-Lago and the polity-centred structure model of Theda Skocpol. Conclusions: Despite relatively similar policy lines implemented in both countries, the contrasting long-term institutional features (Chilean programmes addressed maternal and child health more efficiently than the Argentines) account for most of the variation in the overall process of reform implementation and the performance of maternal and child health policies.